The bird in the Andolesian imprisoning - جمعة, وفاء (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The nature with its two parts the silent and the spoken one occupied an important place in the Arabic literature as it has a direct effect and a strong relationship in the life of man and his different states, so the echves of these appeared clearly in effects of literary men during long periods. The differences of places and the environment, this contained the Arabic poetry many poems which were done for these purposes or the lines of poetry which are mentioned in different subjects by which the poets expressed their psychological, living, social and political states. The description of birds in the Andolesian literature which has a relation of the wonderful side of describing the nature. As it has a psychological, mental and spiritual effects in the life of the Andolesian poet in special and as these creatures have a big effect in the sense of man in general. He used to inspire from the views of birds and their sounds , tunes and movements, many sides of happiness , pain, merriment, unhappiness, optimism and pessimism. The bird was noticed clearly in the poetry of prisons in"Andalos". The imprisoning shows us an important polotical and social side and relects the thinking and psychological condition of the poet and the relation of place for the artistic innovation and its obility to explode the feeling of the poet. The bird formed an important role for this subject which formed with the poet an opposite deut. He lives free while we see the imprisoned poet deprived of his freedom , suffers from the pain and disgrace